Heavy Metals Pollution and Pb Isotopic Signatures in Surface Sediments Collected from Bohai Bay, North China - Bo Gao; Jin Lu; Hong Hao; Shuhua Yin; Xiao Yu; Qiwen Wang; Ke Sun (The Scientific World Journal)
To investigate the characteristics and potential sources of heavy metals pollution, surface sediments collected from Bohai Bay, North China, were analyzed for the selected metals (Cd, Cr, Cu, Ni, Pb, and Zn). The Geoaccumulation Index was used to assess the level of heavy metal pollution. Pb isotopic compositions in sediments were also measured to effectively identify the potential Pb sources. The results showed that the average concentrations of Cd, Cr, Cu, Ni, Pb, and Zn were 0.15, 79.73, 28.70, 36.56, 25.63, and 72.83 mg/kg, respectively. The mean concentrations of the studied metals were slightly higher than the background values. However, the heavy metals concentrations in surface sediments in Bohai Bay were below the other important bays or estuaries in China. The assessment by Geoaccumulation Index indicated that Cr, Zn, and Cd were classified as “the unpolluted” level, while Ni, Cu, and Pb were ranked as “unpolluted to moderately polluted” level. The order of pollution level of heavy metals was: Pb>Ni>Cu>Cr>Zn>Cd. The Pb isotopic ratios in surface sediments varied from 1.159 to 1.185 for 206Pb/207Pb and from 2.456 to 2.482 for 208Pb/207Pb. Compared with Pb isotopic radios in other sources, Pb contaminations in the surface sediments of Bohai Bay may be controlled by the mix process of coal combustion, aerosol particles deposition, and natural sources.